1997
DOI: 10.1111/j.1432-1033.1997.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Studies on Conserved Histidine Residues in the Chlorophyll‐Binding Protein CP43 of Photosystem II

Abstract: Two chlorophyll-binding antenna proteins in the photosystem I1 core, CP43 and CP47, are structurally similar and are thought to have evolved from a common ancestor. Several conserved histidine residues in hydrophobic regions of CP47 have been shown to be important for photosystem I1 structure, function, and energy transfer. The purpose of this study was to determine whether similarly located histidine residues in CP43 function in a similar way. Three conserved histidine residues in presumed membranespanning re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
1
10
1
Order By: Relevance
“…From our results we conclude that CP43 is not required for the water oxidase activity of PSII, although mutational studies have demonstrated its involvement in normal PSII assembly and function in vivo (38)(39)(40). In particular, deletion of the gene encoding CP43 resulted in the assembly of a low level of a CP47RC complex unable to evolve oxygen but showing lightdriven electron transfer from Y Z to Q A (29).…”
Section: Discussionmentioning
confidence: 64%
“…From our results we conclude that CP43 is not required for the water oxidase activity of PSII, although mutational studies have demonstrated its involvement in normal PSII assembly and function in vivo (38)(39)(40). In particular, deletion of the gene encoding CP43 resulted in the assembly of a low level of a CP47RC complex unable to evolve oxygen but showing lightdriven electron transfer from Y Z to Q A (29).…”
Section: Discussionmentioning
confidence: 64%
“…Previous work has shown that the availability of Chl a is important for the synthesis and accumulation of full-length CP47 apopolypeptide (33,34) and that absence of carotenoid leads to impaired synthesis of CP47 and especially of CP43 (35). Also, accumulation of CP47 and CP43 is severely impaired in site-directed mutants lacking an appropriate amino acid ligand to chlorophyll (36,37). These data therefore suggest that binding of pigment starts to occur at an early stage in the assembly of CP47 and CP43 in the WT, perhaps even cotranslationally during insertion of the apopolypeptides into the membrane to help stabilize the complex.…”
Section: Discussionmentioning
confidence: 99%
“…PsbC His119 in Synechocystis sp. PCC 6803 corresponding to His117 in T. elongatus; Manna and Vermaas 1997).…”
Section: Structure Of Antenna Subunits Cp43 and Cp47mentioning
confidence: 99%